(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The purpose and the essence of the doctrine of Kubroviya, which is the main link of Sufism, its mystical-philosophical foundations, the theory of colors and forms of Najmuddin Kubro, his views on "Latoif", the importance of this theory in the spiritual development of a person, the role and importance of Kubrovian ideas in the education of today’s young generation is analyzed from a scientific and philosophical point of view.